Penerapan Metode Praktik Pembuatan Kincir Angin Origami pada Pembelajaran Konsep Perubahan Energi di Kelas IV SDN Gringging 4 - Arvilla Oktaviona; Nazai Rhodiatul Annisa; Massafatul Kuzazah Fauziah (TARBAWIYAT, 2026)
This research aims to describe the implementation of the practical method of making windmills from origami paper on energy transformation material for fourth-grade students at SDN Gringging 4. The primary problem in this research is the low understanding of energy transformation concepts among students, caused by teacher-centered learning and a lack of direct learning experiences, which leads to students' difficulty in explaining the process of energy transformation and relating it to surrounding phenomena. This research uses a descriptive approach with 14 fourth-grade students as the research subjects. Data collection was conducted through observation, interviews, and practical activities. Data were analyzed using the Miles and Huberman analysis model, which includes data reduction, data display, and conclusion drawing. The results showed that the implementation of the practical method increased the activity and enthusiasm of all students (100%); however, there was a gap in conceptual understanding where only 5 students (35.7%) were able to explain the concept well, while the other 9 students (64.3%) still faced difficulties in following the practical steps and relating them to the material. Nonetheless, the practical method helps students understand the concept of energy transformation through direct learning experiences.